Analisis Filsafat dan Implikasi pada Proses Pendidikan - Entoh Tohani (Jurnal Penelitian Pendidikan, 2014)
The use of language in an educational process provides effect to the personality of thelearner. A good language will facilitate substance of education, understood and internalizedby learners. Similarly, teachers who speak politely will lead to the happy feeling forstudents to involve in education. Thus, it is a must in an educational environment; thecommunication process is built based on the truth instead of mendacious communication,without meaninglesness.